Refolding and purification of bothropstoxin-1, a Lys49 - Phospholipase A(2) homologue, expressed as inclusion bodies in Escherichia coli - Ward, R. J.; de Oliveira, AHC; Bortoleto, R. K.; Rosa, J. C.; Faca, V. M.; Greene, L. J. (Academic Press Inc., 2001)
Hydrolysis of phospholipids by Group II phospholipase A(2) enzymes involves a nucleophilic attack on the sn-2 ester bond by the His48 residue and stabilization of the reaction intermediate by a Ca2+ ion cofactor bound to the Asp49 residue in the protein active site region, Bothropstoxin-I (BthTX-I) is a PLA, variant present in the venom of the snake Bothrops jararacussu which shows a Asp49 to Lys substitution and which lacks hydrolytic activity yet damages artificial membranes by a noncatalytic Ca2+-independent mechanism. In order to better characterize this unusual mechanism of membrane damage, we have established an expression system for BthTX-I in Escherichia coli. The DNA-coding sequence for BthTX-I was subcloned into the vector pET11-d, and the BthTX-I was expressed as inclusion bodies in E, coli BL21(DE3). The native BthTX-I contains seven disulfide bonds, and a straightforward protocol has been developed to refold the recombinant protein at high protein concentration in the presence of surfactants using a size-exclusion chromatography matrix. After refolding, recovery yields of 2.5% (corresponding to 4-5 mg of refolded recombinant BthTX-I per liter of bacterial culture) were routinely obtained. After refolding, identical fluorescent and circular dichroism spectra were obtained for the recombinant BthTX-I compared to those of the native protein. Furthermore, the native and refolded recombinant protein demonstrated identical membrane-damaging properties as evaluated by measuring the release of an entrapped fluorescent marker from liposomes, (C) 2001 Academic Press.